Effect of one-year corrosion on steel bridge materials in the maintenance stage with the Charpy impact test method - Fauzri Fahimuddin; Mudiono Kasmuri; Rikki Sofyan; Syarif Junaidi; Latha MS (SINERGI, 2023)
Corrosion of steel bridges is a major problem because it has the potential to reduce the performance of the structure over its lifetime. One factor that should not be reduced is fracture toughness, so this should be a very important concern in the maintenance program. Existing guidelines do not specify when corrosion conditions are hazardous and when corrosion conditions are not hazardous to structural performance. This study aims to explain how long corrosion does not cause danger, and when corrosion becomes dangerous. The Charpy Impact Test was used in this study to examine the effect of corrosion with a corrosion duration of weekly up to one year on fracture toughness. The series of tests in this research program used SM-490-type specimens which are steel plates commonly used for bridge structures. Specimens with variations in corrosion duration which were the result of immersion in sulfuric acid solution to simulate corrosion growth were then subjected to crack toughness testing. The toughness of each specimen was tested with a corrosion period starting from 1 week and so on up to 1 year to determine the level of fracture toughness. The results obtained from all tests showed that there was no decrease in the toughness of the corroded specimens for up to 1 year. The data presented in this study is very helpful for the designers and maintainers to plan corrosion treatment programs with clearer and more accurate considerations in assessing the structural integrity of steel bridges affected by corrosion.